Coal geology - Thomas, Larry (Larry P.) (Chichester, West Sussex ; Hoboken, NJ : John Wiley & Sons, 2013)
Coal Geology, second edition, offers a thoroughly revised and updated edition of this popular book which provides a comprehensive overview of the field of coal geology. Coal Geology covers all aspects of coal geology in one volume, bridging the gap between the academic aspects and the practical role of geology in the coal industry. The object of the book is to provide the reader with a with a description of the origins of coal together with the physical and chemical properties of coal and coal petrology before proceeding to cover all areas of coal exploration, production and use. Bridges the gap between academic aspects of coal geology and the practical role of geology in the coal industry ; Examines historical and stratigraphical geology, together with mining, environmental issues, geophysics and hydrogeology and the marketing of coal ; Defines worldwide coal resource classifications and methods of calculation ; Addresses the alternative uses of coal as a source of energy, together with the environmental implications of coal usage ; Includes improved illustrations including a colour section ; Offers a global approach covering expanding fields in America, China and India. The truly global approach, drawn from the international experiences of the author, recognizes the growing role of coal use in emerging markets. With fully revised coverage of the latest modelling techniques, environmental legislation, equipment and recording methods, the second edition offers a truly invaluable resource for anyone studying, researching or working in the field of coal geology, geotechnical and mining engineering and environmental science.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Coal -- Geology; TECHNOLOGY & ENGINEERING -- Power Resources -- Fossil Fuels; Coal -- Geology; Electronic books; Electronic books